Diversity of bacterial communities in bacterial wilt-diseased banana plants / Nurul Shamsinah Mohd Suhaimi - Nurul Shamsinah, Mohd Suhaimi (2017)
The major constraint of banana production worldwide is the capacity of this crop to withstand pest and disease pressures, such as the bacterial wilt disease. In Malaysia, this disease inflicts major losses on our banana industry. Hence, initial attempt was made to detect, isolate and identify the pathogenic bacteria associated with bacterial wilt-diseased banana plants from six sampling locations around the Peninsular Malaysia. This study was further extended to identify the abundantly isolated bacterial colonies, followed by determination of the biofilm-forming ability of the identified strains. Four strong biofilm-forming strains, identified as Enterobacter cloacae, Enterobacter hormaechei, Klebsiella pneumonia and Kosakonia radicincitans were inoculated as mono- and co-cultured with the blood disease pathogenic strain, Ralstonia syzygii subsp. celebesensis into two months-old banana plants. A strong biofilm-forming strain with synergistic effects on the severity of disease symptoms was then chosen for the whole genome sequence analyses. A 16S rRNA gene sequencing metagenomics was carried out to determine bacterial communities in the symptomatic and non-symptomatic bacterial wilt-diseased banana plants. Based on the conventional method, bacteria associated with diseased banana plants were identified as Enterobacter, Klebsiella, Pseudomonas, Kosakonia and Burkholderia. Nine out of twelve isolates were identified as strong biofilm-formers. In-vivo assessment of mono- and co-inoculations of four strong biofilm-formers with pathogenic strain indicated that the plants co-inoculated with K. radicincitans and R. syzygii subsp. celebesensis were most highly susceptible to the disease. Meanwhile, plants under two treatments (co-inoculation of R. syzygii subsp. celebesensis with E. cloacae and E. hormaechei, respectively) were less susceptible. Genome sequence analyses of the K. radicincitans UMEnt01/12 had identified various genes related to survivability, adhesion, colonization and synergistic interactions of the bacterium. The 16SrRNA gene sequencing metagenomics analyses further indicated that higher diversity and abundance were detected in the non-symptomatic plant as compared to the symptomatic plants. These findings suggest that the presence of biofilm-forming bacteria in diseased plants might synergistically or antagonistically affect the severity of infection caused by the pathogen. The whole genome sequence analyses had provided insights into the mechanisms of colonization, establishment and interactions with the host plant and pathogen in the vascular tissues of diseased banana plant. The diversity of bacterial populations could be associated with physiological status of the plants and this could affect the susceptibility of plants towards bacterial wilt disease. Taken together, this study implies the concepts of synergism and antagonism among the pathogen and endophytes in the diseased banana plants which may affect the occurrence and progression of disease symptoms. Although the varying abundance and diversity of the bacterial communities in both non-symptomatic and symptomatic plants could not possibly determine the contribution of the microbiota towards different plants physiological status and condition, the study had indicated comparable differences in the biodiversity of microbiota in the symptomatic and non-symptomatic bacterial wilt-diseased banana plants.